2021
DOI: 10.3390/microbiolres12010016
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Pangenomics of SARS-CoV-2 Isolates Reveal Evidence for Subtle Adaptive Expression Strategies, Continued Clonal Evolution, and Sub-Clonal Emergences, Despite Genome Stability

Abstract: The devastating SARS-CoV2 pandemic is worsening with relapsing surges, emerging mutants, and increasing mortalities. Despite enormous efforts, it is not clear how SARS-CoV2 adapts and evolves in a clonal background. Laboratory research is hindered by high biosafety demands. However, the rapid sequence availability opened doors for bioinformatics. Using different bioinformatics programs, we investigated 6305 sequences for clonality, expressions strategies, and evolutionary dynamics. Results showed high nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…For instance, the enhanced epidemicity has resulted in a total of 312,173,462 confirmed cases of COVID-19 globally, including 5,501,000 deaths reported to the World Health Organization (WHO) as of 12 January 2022 (available at ; accessed on 12 January 2022). The increased human–human transmission has caused the re-emergence of variants and sub-clonal populations in different regions despite the clonal genome [ 1 , 2 ]. However, an unprecedented global effort led to efficient vaccine products such as Pfizer Biontech, Moderna, and AstraZeneca.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the enhanced epidemicity has resulted in a total of 312,173,462 confirmed cases of COVID-19 globally, including 5,501,000 deaths reported to the World Health Organization (WHO) as of 12 January 2022 (available at ; accessed on 12 January 2022). The increased human–human transmission has caused the re-emergence of variants and sub-clonal populations in different regions despite the clonal genome [ 1 , 2 ]. However, an unprecedented global effort led to efficient vaccine products such as Pfizer Biontech, Moderna, and AstraZeneca.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV2 genome has a high rate of recombination and adaptive expression strategies which allows them to pass into and infect several hosts through variety of environmental niches. Several studies have shown viral variations at different geographical locations like Southeast Asian (Maurya et al, 2021), European (Hryhorowicz et al, 2021) and North American nations (Attwood et al, 2022), and globally (Said et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 genome has a high rate of recombination and adaptive expression strategies which allows them to pass into and infect several hosts through variety of environmental niches. Several studies have shown viral variations at different geographical locations like Southeast Asian [ 14 ], European [ 15 ] and North American nations [ 16 ], and globally [ 17 ].…”
Section: Introductionmentioning
confidence: 99%